Solitary fibrous tumor of the pleura mimicking pleural effusion - Borges, Flávia Kessler; Dornelles, Caroline Machado Rotta; Vivian, Analu (Clinical and Biomedical Research, 2015)
Solitary fibrous tumor of the pleura is a rare mesenchymal neoplasm of fibroblastic origin and represents less than 5% of primary tumors of the pleura. There are few reports in the literature about this disease, therefore the data on its presentation and management are derived from reports and retrospective analysis of case series from referral centers. In this report, we describe a case of a patient who presented this diagnosis during hospitalization, and following we briefly review the published literature of this pathology.